Exploring sociodemographic characteristics, sleep quality, food group consumption, and body weight status among university students during the COVID-19 movement restriction - Mohd Saliza, Wan Afiqah Nadhrah; Ibrahim, Zuriati (Galore Knowledge Publication, 2024)
The COVID-19 pandemic has profoundly affected lifestyles, including sleep quality, dietary habits, and body weight status. This cross-sectional study investigated the associations between sociodemographic characteristics, sleep quality, food group consumption with body weight status among university students during Malaysia’s Movement Control Order (MCO). An online survey was conducted with 145 participants, aged 19-24 years old between June - Aug 2021. Data on socio-demographics, sleep quality, food group consumption, and self-reported anthropometric measures were collected. The findings showed 46.2% had normal weight, 37.2% were overweight or obese, and 16.6% were underweight. Majority being 22 years old (80%), female (91.7%), and of Malay ethnicity (93.1%). Sleep quality was reported as fairly good by 44.1% of respondents, and beverages were the most consumed food group (median: 5.42 servings/day). Age was positively correlated with body mass index (BMI) (r=0.179, p<0.05), while dietary intake of cereals and cereal products showed a significant positive association with BMI (r=0.435, p<0.05). Conversely, fish and seafood consumption was inversely associated with BMI (r=-0.185, p<0.05). No significant association was observed between sleep quality and BMI. In conclusion, age and specific dietary patterns, particularly the consumption of cereals and fish, were significant factors associated with body weight status during the MCO period. These findings highlight the need for targeted nutritional education and interventions to promote balanced dietary habits, especially during periods of restricted mobility, to mitigate potential adverse effects on body weight and overall health.